The method of monitoring of thermodynamic efficiency of heat pump - Клепанда, Александр Сергеевич; Тарасова, Виктория Александровна; Бережко, Юлия Викторовна (Eastern-European Journal of Enterprise Technologies, 2014)
A technique for monitoring the heat pump, which allows for a limited amount of measured parameters exercise testing its thermodynamic efficiency in real time. Methodology includes three stages: the first stage - monitoring, involving only data logging and collection of information about the operation of the heat pump, the second stage - the processing of monitoring data, and the third stage - the analysis and diagnosis of the thermodynamic efficiency. The results of monitoring of the heat pump series Vicot VMN430L in the heating system of the administrative building is present. Monitoring system recorded the following parameters: temperature and humidity of the outside air temperature in the "direct" and "inverse" highways of the heating system, the power consumption of compressors , water flow in the condenser of the heat pump. Found that the model holds VMN430L low efficiency at low ambient temperatures that the current generation of chillers and heat pumps from other manufacturers is not so typical.